Yeast surface display identifies a family of evasins from ticks with novel polyvalent CC chemokine-binding activities - Singh, Kamayani (Sci Rep, 2017)
Chemokines function via G-protein coupled receptors in a robust network to recruit immune cells to sites of inflammation. Due to the complexity of this network, targeting single chemokines or receptors has not been successful in inflammatory disease. Dog tick saliva contains polyvalent CC-chemokine binding peptides termed evasins 1 and 4, that efficiently disrupt the chemokine network in models of inflammatory disease. Here we develop yeast surface display as a tool for functionally identifying evasins, and use it to identify 10 novel polyvalent CC-chemokine binding evasin-like peptides from salivary transcriptomes of eight tick species in Rhipicephalus and Amblyomma genera. These evasins have unique binding profiles compared to evasins 1 and 4, targeting CCL2 and CCL13 in addition to other CC-chemokines. Evasin binding leads to neutralisation of chemokine function including that of complex chemokine mixtures, suggesting therapeutic efficacy in inflammatory disease. We propose that yeast surface display is a powerful approach to mine potential therapeutics from inter-species protein interactions that have arisen during evolution of parasitism in ticks.